DELEGATED POWER, CAPTURED GOVERNANCE : HOW WEAKNESSES IN ADMINISTRATIVE ACCOUNTABILITY FUEL CRONY CAPITALISM AND SOCIAL INEQUALITY - Vu Minh, Chau (International Journal of Law in Changing World, 2025)
The modern administrative state relies extensively on delegated legislation to address complex governance challenges, yet this reliance creates fundamental democratic accountability deficits. This paper argues that inadequate oversight mechanisms in delegated legislation processes create systematic vulnerabilities to crony capitalism and state capture, thereby exacerbating social inequality. Through theoretical synthesis and doctrinal analysis of administrative law principles, this research demonstrates how weak parliamentary scrutiny, limited judicial review, and insufficient public participation enable private interests to manipulate regulatory processes for personal advantage. The paper presents evidence showing that captured administrative decision-making systematically redirects public resources away from broad social welfare toward narrow elite interests, thereby reinforcing existing inequality structures. The research contributes a comprehensive framework linking administrative law design flaws to broader political economy pathologies and their social consequences, offering theoretical insights for administrative reform aimed at strengthening democratic governance and reducing inequality. __________ PODER DELEGADO, GOBERNANZA CAPTURADA: CÓMO LAS DEBILIDADES EN LA RENDICIÓN DE CUENTAS ADMINISTRATIVA IMPULSA EL CAPITALISMO DE AMIGOS Y LA DESIGUALDAD SOCIAL El Estado administrativo moderno depende en gran medida de la legislación delegada para abordar los complejos desafíos de gobernanza; sin embargo, esta dependencia genera déficits fundamentales de rendición de cuentas democrática. Este artículo argumenta que los mecanismos de supervisión inadecuados en los procesos de legislación delegada generan vulnerabilidades sistemáticas al capitalismo de amiguismos y a la captura del Estado, lo que posteriormente exacerba la desigualdad social. Mediante una síntesis teórica y un análisis doctrinal de los principios del derecho administrativo, esta investigación demuestra cómo el escrutinio parlamentario deficiente, la revisión judicial limitada y la participación pública insuficiente permiten que los intereses privados manipulen los procesos regulatorios para obtener beneficios personales. El artículo presenta evidencia que demuestra que la toma de decisiones administrativas capturadas redirige sistemáticamente los recursos públicos del bienestar social hacia intereses de élite, reforzando así las estructuras de desigualdad existentes. La investigación aporta un marco integral que vincula las fallas de diseño del derecho administrativo con patologías más amplias de la economía política y sus consecuencias sociales, ofreciendo perspectivas teóricas para la reforma administrativa destinada a fortalecer la gobernanza democrática y reducir la desigualdad. __________ 权力下放，治理沦陷：行政问责机制的薄弱如何助长裙带资本主义和社会不平等 现代行政国家广泛依赖授权立法来应对复杂的治理挑战，然而这种依赖却造成了根本性的民主问责缺陷。本文认为，授权立法过程中监督机制的不足，使得国家容易受到裙带资本主义和权力攫取的影响，进而加剧社会不平等。通过对行政法原则的理论综合和教义分析，本文揭示了议会监督薄弱、司法审查有限以及公众参与不足如何使私人利益集团得以操纵监管程序以谋取私利。本文提供的证据表明，被权力攫取的行政决策系统性地将公共资源从广泛的社会福利转向狭隘的精英利益，从而强化了现有的不平等结构。该研究构建了一个综合框架，将行政法设计缺陷与更广泛的政治经济弊病及其社会后果联系起来，为旨在加强民主治理和减少不平等的行政改革提供了理论见解。